Self Efficacy dengan Academic Dishonesty pada Mahasiswa Universitas Putra Indonesia “YPTK” Padang - Isna Asyri Syahrina (Universitas Negeri Padang, 2016)
Abstrack: Self eficacy with academic dishonesty on students at the University Putra Indonesia